2010
DOI: 10.1016/j.bbmt.2010.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Unrelated Transplantation for Poor-Prognosis Adult Acute Lymphoblastic Leukemia: Long-Term Outcome Analysis and Study of the Impact of Hematopoietic Graft Source

Abstract: Adults with high-risk acute lymphoblastic leukemia (HR-ALL) have a poor outcome with standard chemotherapy and usually undergo unrelated stem cell transplantation (SCT) if a matched sibling donor is not available. We analyzed the outcome of adult patients with unrelated SCT for HR-ALL and studied the possible effect of the hematopoietic stem cell source of the transplant. A total of 149 adult patients (median age, 29 years, range, 15-59 years) with HR-ALL underwent unrelated SCT in 13 Spanish institutions betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…The Spanish group has reported outcomes of 62 high-risk ALL patients receiving UCBT compared with 87 transplanted with matched unrelated donor grafts, with no significant differences in RI, LFS or OS. 12 Data on outcomes after UCBT for ALL adult patients are scarce. [13][14][15] One Japanese series reported in 2009 outcomes of Abbreviations: cGVHD = chronic GVHD; LFS = leukemia-free survival; RIC = reduced intensity conditioning; UCBT = unrelated cord blood transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Spanish group has reported outcomes of 62 high-risk ALL patients receiving UCBT compared with 87 transplanted with matched unrelated donor grafts, with no significant differences in RI, LFS or OS. 12 Data on outcomes after UCBT for ALL adult patients are scarce. [13][14][15] One Japanese series reported in 2009 outcomes of Abbreviations: cGVHD = chronic GVHD; LFS = leukemia-free survival; RIC = reduced intensity conditioning; UCBT = unrelated cord blood transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Different comparative studies on stem cell sources reported similar outcomes after unrelated donor allo-HSCT or unrelated CB transplantation (UCBT) for adults with acute leukemias. [8][9][10][11][12] To date, only a few studies have critically assessed the overall outcomes after UCBT for adult ALL. [13][14][15] To describe outcomes and risk factors after UCBT for adult ALL, with the aim to evaluate whether it is a suitable option to treat this population, we designed a retrospective registry-based analysis including 421 patients who received UCBT in European group for blood and marrow transplantation (EBMT) centers.…”
Section: Introductionmentioning
confidence: 99%
“…1 Results using alternative stem cell sources or alternative donors have improved in the last decade, and current outcomes after HSCT are strongly correlated with clinical disease status. [2][3][4][5] The optimal results in both children and adults are obtained when patients underwent HSCT at early stages of the disease as measured by conventional morphological remission. [5][6][7] Over the last decade, the concept of remission in ALL has evolved owing to use of molecular techniques and multiparameter flow cytometry (MFC) to more precisely track residual leukemic cells during chemotherapy treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that unrelated HSCT may be effective for high-risk adult ALL patients in various disease statuses. 31,32 In addition, two retrospective studies showed no difference between related and unrelated HSCT for adult ALL patients, including those in CR1, 12,13 and the recent evidencebased review from the American Society for Blood and Marrow Transplantation supported this. 33,34 However, patients who undergo unrelated HSCT in CR1 are a select population of patients who have maintained their remission status during the donor-coordination process.…”
Section: Discussionmentioning
confidence: 87%